Kitap Değerlendirmesi: Abderrazak Halloumi, Le Livre de l’eschiele Mahomet: Un manuel d’islamologie au XIIIe siècle (Paris: Classiques Garnier, 2024)/Review of Le Livre de l’eschiele Mahomet: Un manuel d’islamologie au XIIIe siècle by Abderrazak Halloumi (Paris: Classiques Garnier, 2024) - Murat Çaylı (Oksident, 2025)
Livre de l'Eschiele Mahomet, one of the important works that shaped the perception of Islam by Christians in Western Europe in the 13th-century, was translated into Castilian by order of King Alfonso X in the 1260s. A few years later it was also translated into French and Latin. The focal point of the work is the events of Isra and Miraj. However, since it also provides information about the Prophet Muhammad and Islam, it was regarded as the second holy book of Muslims in Andalusia after the Qur’an. In this work, Abderrazak Halloumi analyses the Livre de l'Eschiele Mahomet, which was created in the 13th-century on the basis of the events of Isra and Miraj, but which is actually a work of Islamic research. In addition to Miraj, the work, which also provides information about the angelic world, death, judgement, Paradise, Hell, etc. according to Islam, was compiled using many Islamic sources. The author, who tried to identify these sources, benefited from the copies of Kitāb al Miraj, the Qur'an, tafsirs, hadiths, eschatological works, the Bible and other theological texts.